A Review : Utilization of By-Products from Areca Nut and Coconut Processing as Environmentally Friendly Biobriquettes - Ade Yulia; Dompak MT Napitupulu; Sahrial; Addion Nizori (Green Engineering Society, 2026)
Large quantities of by-products from areca nut and coconut processing generated annually have significant potential as solid fuel feedstocks due to their high lignocellulosic content. Optimal utilization of these residues can increase their added value and reduce the environmental impacts associated with organic waste. This study aimed to explore the manufacturing process and characteristics of biobriquettes made from biomass waste in the form of areca nut husk, coconut husk, and coconut shell. These raw materials were processed through the stages of cleaning, drying, carbonation, refining, mixing with adhesives, molding, and drying. The use of adhesives such as tapioca flour, sago, or palm oil liquid waste affects the quality of biobriquettes, including their moisture content, ash content, calorific value, density, and combustion rate. The results of the study revealed that biomass-based biobriquettes have several advantages, such as being cost-effective, environmentally friendly, and producing a high calorific value. This study provides scientific and practical benefits to the processing of biomass waste into renewable energy with high economic value. The utilization of this waste not only enhances renewable energy production but also reduces agricultural waste and environmental pollution.